A survey on integrity verification and data auditing schemes for data verification in remote cloud servers. (2017) - Muthuram, R.; Kousalya, G.
Cloud computing is the opportunistic model that provides a lot of services to the business organisations to concentrate more on their own business services instead of spending more cost on maintenance. The service providers provide an unlimited storage capability to the clients with characteristics like scalability, reliability, on-demand self-service etc. Clients host their data on cloud servers and pay the cost based on their usage. The data consumers can access the data from the cloud servers. Because of lack of access control and data may tamper by malicious users, business organisations hesitating to use the cloud computing. Ensuring the data storage correctness and integrity is one of the major issues in the cloud computing. In this paper, we discussed the various integrity system models that are available and the procedure for the various existing integrity verification schemes proposed. Finally, those schemes are analysed in terms of security and performance.